Doktrin Pentingkah? : Minimnya Pemahaman Jemaat Gereja-Gereja Protestan Di Sumatera Utara Tentang Doktrin-Doktrin Dasar Dalam Kekristenan - Fernando Tambunan (Sekolah Tinggi Teologi Baptis Medan, 2022)
Christianity in North Sumatra has been running for more than 190 years, but it is suspected that the congregation's understanding of the doctrine is very low. For the congregation in general there is an opinion that doctrine is not important, especially for people today who tend to build a pragmatic culture, generally today's Christians don't really like complicated things, they want things that are simple and easy. Many Christians think that doctrinal issues are the business of the priests or those who go to theological schools. The method used in this research is to observe congregations in Protestant churches in North Sumatra to see the extent of their understanding, and is supported by theory through descriptive methods with a qualitative approach by looking at the literature. It was found that many congregations in North Sumatra have a shallow understanding of the doctrine. It is the responsibility of every believer to learn doctrine, so that he can grow and not be easily tossed about by various winds of teaching. For this reason, the congregation needs to be equipped with a good doctrinal understanding through continuous training/debriefing